The utility of massively parallel sequencing for posterior polymorphous corneal dystrophy type 3 molecular diagnosis - Dudakova, Lubica; Evans, Cerys J; Pontikos, Nikolas; Hafford-Tear, Nathaniel J; Malinka, Frantisek; Skalicka, Pavlina; Horinek, Ales; Munier, Francis L; Voide, Nathalie; Studeny, Pavel; Vanikova, Lucia; Kubena, Tomas; et al. (Experimental eye research, 2019)
The aim of this study was to identify the molecular genetic cause of disease in posterior polymorphous corneal dystrophy (PPCD) probands of diverse origin and to assess the utility of massively parallel sequencing in the detection of ZEB1 mutations. We investigated a total of 12 families (five British, four Czech, one Slovak and two Swiss). Ten novel and two recurrent disease-causing mutations in ZEB1, were identified in probands by Sanger (n = 5), exome (n = 4) and genome (n = 3) sequencing. Sanger sequencing was used to confirm the mutations detected by massively parallel sequencing, and to perform segregation analysis. Genome sequencing revealed that one proband harboured a novel ∼0.34 Mb heterozygous de novo deletion spanning exons 1-7 and part of exon 8. Transcript analysis confirmed that the ZEB1 transcript is detectable in blood-derived RNA samples and that the disease-associated variant c.482-2A>G leads to aberrant pre-mRNA splicing. De novo mutations, which are a feature of PPCD3, were found in the current study with an incidence rate of at least 16.6%. In general, massively parallel sequencing is a time-efficient way to detect PPCD3-associated mutations and, importantly, genome sequencing enables the identification of full or partial heterozygous ZEB1 deletions that can evade detection by both Sanger and exome sequencing. These findings contribute to our understanding of PPCD3, for which currently, 49 pathogenic variants have been identified, all of which are predicted to be null alleles.
Keywords: exony; Sequence Deletion; Young Adult; DNA Mutational Analysis; sekvence nukleotidů; heterozygot; sekvenční delece; transkripční faktor Zeb1; Pedigree; mutace; Child, Preschool; Posterior polymorphous corneal dystrophy type 3; rodokmen; dědičné dystrofie rohovky; ZEB1; Heterozygote; mladý dospělý; High-Throughput Nucleotide Sequencing; Adolescent; Exons; Child; Aberrant splicing; Zinc Finger E-box-Binding Homeobox 1; Breakpoint mapping; dítě; Adult; zinkové prsty; Aged; dospělí; senioři; Massively parallel sequencing; mutační analýza DNA; mladiství; předškolní dítě; lidé; Zinc Fingers; Exome; Humans; vysoce účinné nukleotidové sekvenování; Corneal Dystrophies, Hereditary; DNA; Base Sequence; Genome; Mutation; lidé středního věku; Middle Aged